When Management Matters More than Leadership. Issue 4 (12th March 2021) - Ponomariov, Branco; Boardman, Paul; Boysen, Rebecca
ABSTRACT: This study uses the data from the Federal Employee Viewpoint Survey for the Federal Department for Health and Human Services to observe the effects of the perceived leadership style initiating structure (which emphasizes conventional management) and consideration (which emphasizes leader-subordinate relations and trust) on federal employees' turnover intention. The results suggest that the former reduces the likelihood of turnover intention where the latter does not, when controlling for job satisfaction and other important factors. Implications for theory and practice are discussed.